Comparative Study for The Removal of Hg(II) From Aqueous Solutions by Adsorption on The Gum Arabic and Modified Gum Arabic - Arvand, M.; Shemshadi, R.; Efondiov, A.A.; Zeynalov, N.A.; Latify, L.; Pourhabib, A.; Farnoosh, R. (Asian Journal of Chemistry, 2010)
In the present investigation, gum arabic (GA) and glycidyl methacrylate modified gum arabic (GMA-GA) were assessed as biosorbents for the removal of Hg(II) from aqueous solutions. For chemical modification of gum arabic with glycidyl methacrylate, an appropriate mixture of water and DMSO was used to dissolve gum arabic and glycidyl methacrylate. The approving of chemical modification and the presence of glycidyl methacrylate groups in the modified structure of gum arabic (GMA-GA) was confirmed by diffuse reflectance spectroscopy (DRS). The equilibrium studies are systematically carried out in a batch process, covering various process parameters that include agitation time, adsorbent dosage and pH of the aqueous solution. It was observed in adsorption and desorption tests that GMA-GA showed significant pH dependence, which affected the removal efficiency, robustly. Adsorption behaviour is found to follow Freundlich and Langmuir isotherms. The adsorption mechanism is described by a pseudo second order kinetics. A regeneration study was also carried out.